Sensitive on-site detection of SARS-CoV-2 by ID NOW COVID-19. (August 2021) - Krause, Eva; Puyskens, Andreas; Bourquain, Daniel; Brinkmann, Annika; Biere, Barbara; Schaade, Lars; Michel, Janine; Nitsche, Andreas
Abstract: Point of care detection of SARS-CoV-2 is one pillar in a containment strategy and important to break infection chains. Here we report the sensitive, specific and robust detection of SARS-CoV-2 and respective variants of concern by the ID NOW COVID-19 device. Highlights: The ID NOW COVID-19 device enables SARS-CoV-2 genome detection down to 800 genome copies per mL. The 50% detection probability is 3, 700 genome copies per mL. Time to result is approximately 13 minutes for negative specimens. Analytical specificity is 100% as shown by negative specimens and specimens containing 16 different respiratory viruses.